2020
DOI: 10.1177/0734242x20911708
|View full text |Cite
|
Sign up to set email alerts
|

Public views and attitudes about municipal waste management: Empirical evidence from Athens, Greece

Abstract: One of the major problems of modern cities is waste management. Cooperation and active public participation are key elements in the effective implementation of waste management programs. The purpose of this work is to investigate the views and attitudes of Athens residents towards recycling, composting and the operation of green centers, which are the key elements of solid waste management as it follows from the recently updated National Waste Management Plan. A structured questionnaire was designed and addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 27 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…The transmission and new emergence of infectious diseases [34]; the highly rated air pollution and environmental protection in the present study reveals the increased environmental awareness of Greek citizens, which is also supported by Drimili et al, who showed a high rate of recycling practice by Athens' residents [35].…”
supporting
confidence: 83%
“…The transmission and new emergence of infectious diseases [34]; the highly rated air pollution and environmental protection in the present study reveals the increased environmental awareness of Greek citizens, which is also supported by Drimili et al, who showed a high rate of recycling practice by Athens' residents [35].…”
supporting
confidence: 83%
“…Most waste policy interventions are devoid of coproduction in terms of understanding the user’s needs and situations and involving them in formulating strategies to resolve household recycling issues ( Alfaia et al, 2017 ; Sewak et al, 2021 ). The non-involvement of citizens in formulating waste policies and strategies has resulted in public distrust in government waste policies, and thus a barrier to effective implementation of such policies ( Drimili et al, 2020 ; Pollans, 2017 ). The majority of the citizens doubt whether the materials collected are genuinely recycled; many believed the materials are burned to generate electricity just like the rubbish collected, hence questioning the need to separate recyclable waste from non-recyclable waste.…”
Section: Resultsmentioning
confidence: 99%
“…The use of questionnaires in surveys is an effective way to discover the opinion and habits of citizens. They are frequently used in several environmental issues, such as climate change [23,24], energy use [25,26], water or waste management [27][28][29], or other environmental issues [30][31][32]. Even if there are several studies in the literature related to plastics, such as advantages/disadvantages of plastics, environmental impacts from the use of plastics and management of plastics at the end of life [33,34], few papers deal with the opinion of citizens about the use of single-use plastics [35,36].…”
Section: Introductionmentioning
confidence: 99%